Historiography and the political participation of the masses: the "decay" of the Athenian democracy in fourth-century BC - Paiaro, Diego; Requena, Mariano (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2019)
The features of the Athenian democracy and particularly the implications of the full political incorporation of the «poor» have been subjected to the full attention of several modern intellectuals interested in the history of Athens. Mainly concerned with the consequences related to the development of the popular sovereignty and by the growing influence of the popular classes as a relevant political factor, modern political philosophy and traditional historiography have tended to relate the political incorporation of the masses with the Athenian “crisis” and its “decline”. In this paper, this interpretative tradition is critically analysed from our contemporary context.
Keywords: Ancient Athens; Democracy; Crisis; Historiography